Gender Equality and Climate Change - Hailemariam, Abebe; Kalsi, Jaslin; Mavisakalyan, Astghik (2023)
Climate change is having a significant negative impact on the lives of individuals around the globe. But this impact is not distributed equally. A growing body of research suggests that women are more vulnerable to the negative impacts of climate change than men due to socio-economic structures and norms. On the other hand, there is evidence to suggest that improvements in gender equality might benefit climate resilience, suggesting the possibility that efforts to improve gender equality may set a virtuous circle in action. This chapter reviews the literature on both sides of the climate change–gender inequality nexus. First, we explore the evidence of the impact of climate change on a wide range of women’s outcomes. Then, we summarise the evidence on women’s empowerment and climate change action. We conclude with a discussion of implications for policy.